Smart Financial Management for Cooperatives: A Web and Payment Gateway Integration Approach - Ridho Hakiki; Vera Irma Delianti; Rizkayeni Marta; Juan Luis Cabanillas-García; Vladislav Deyanov Slavov; Siti ‘Afiat Jalil (Journal of Hypermedia & Technology-Enhanced Learning, 2025)
This study introduces a web-based application for savings and loan cooperatives, integrating a payment gateway to streamline financial transactions and improve operational efficiency. Developed using the waterfall methodology, the application enables members to deposit savings, apply for loans, and make installment payments online. Key features include automated financial reporting, secure transaction processing, and accessibility for cooperative managers and members. Black-box testing validated that the system met all functional requirements, ensuring reliable and secure operations. The application reduces operational workload, improves service quality, and supports real-time financial transparency by automating administrative tasks and offering multiple payment options—such as bank transfers and e-wallets. This solution demonstrates significant potential for transforming cooperative financial management by providing a scalable, user-friendly, and secure platform that enhances member services and promotes operational sustainability.